Investigation on the Structural Behaviour of GFRP Laminated BFRC Beams - Arulanandam, Preethy Mary; Shimpi, Vinay; Eswari, Eswari (Civil Engineering Dimension, 2025)
This study attempts to investigate the performance of the reinforced concrete beam by using basalt fibre reinforced concrete (BFRC) and glass fibre reinforced polymer (GFRC) as external strengthening. For this purpose, four beams with different strengthening were cast and tested under four-point bending tests. The performance of the beams was compared in terms of mid-point deflection, flexural strength, ductility and failure modes. Additionally, finite element models of the beams have been developed to simulate the behaviour of the strengthened beams. Subsequently, the finite element results were compared with the experimental results and were found to be in good agreement. Finally, the experimental testing and numerical results showed that the flexure capacity of the reinforced concrete beams was enhanced for GFRP strengthening and reduction in the deflection of the beams was observed for BFRC.